UNIVERSAL HEALTH COVERAGE IN MATERNAL AND CHILD HEALTH: KNOWLEDGE, PERCEPTION AND EXPERIENCES OF THE POOREST HOUSEHOLDS - Wenang, Supriyatiningsih; Lidia Febrianti2; Oryzati Hilman3; Pramitha Esha; Frenia Nababan; Dianita Sugiyo (Malaysian Journal of Public Health Medicine, 2024)
The Indonesia’s National Health Insurance Scheme (JKN) administered by Social Security Agency for health (BPJS Kesehatan) is aimed to provide social protection in health sector for all Indonesian citizens. Some challenges remain exist especially to the poorest household related to maternal and child health services. This study aimed to assess knowledge, perception and experiences of the poor households and near poor toward the implementation of JKN, especially related to the utilization of JKN Scheme, Maternal Health- Related Behaviors and Maternal and Child Health Care. This research used mix method study. Quantitative study to provide information on knowledge, perception and experiences of the poor toward implementation of JKN. Qualitative study conducting face-to-face interviews with several key informants.The survey applied the quota sampling method and total respondents were 815 in DIY Province. The respondents encompassed pregnant women, parents of under 5-year-old children and homeless people. Most of knowledge, perception, and experiences about complicated administration procedures is one constraints that hinder the poor and marginal groups to be JKN (national health insurance) members. In terms of the JKN Scheme, it was found that data on the utilization of access to antenatal care using JKN was still limited (48.5%). Maternal Health-Related Behaviors on respondents with higher income levels have a lower percentage of exclusive breastfeeding. While Maternal and Child Health Care in the majority of JKN respondents use the primary health center as a place for pregnancy, childbirth and postpartum services. The government have to improve health services based on knowledge, perception and experiences of poorest households about JKN (national health insurance) implementation.